The effects of hoarding disorder on families: an integrative review. Issue 6 (21st July 2013) - Büscher, T. P.; Dyson, J.; Cowdell, F.
<x xml:space="preserve">Abstract</x> Accessible summary It is estimated that between 2% and 5% of the population experience symptoms of compulsive hoarding. Recent investigation into hoarding has shown that it is a problem in its own right and is therefore being added to a diagnostic manual of mental disorders. This integrative literature review examines the impact that hoarding has on family members. The comprehensive literature review spans a period from database inception to November 2012. A search of the databases Cumulative Index to Nursing and Allied Health Literature, Medical Literature Analysis and Retrieval System Online, and psycINFO, together with hand searches, was completed. Thematic analysis revealed three overriding themes: quality of life, shattered families and rallying around. These themes illuminate the negative impact that hoarding behaviour has on families and the inadequacy of available services. The relative lack of robust evidence about the impact of hoarding behaviour on families suggests that further research is needed in this emergent field. Abstract Compulsive hoarding affects approximately 2–5% of the adult population. Increasing recognition has led to its inclusion as a distinct condition in forthcoming revisions to the Diagnostic and Statistical Manual V. Hoarding behaviour can have a detrimental effect on the health and well‐being of family members. A rigorous review of available evidence using a novel three‐stage literature search was undertaken: (1) an extensive scoping review; (2) a traditional search of databases including Cumulative Index to Nursing and Allied Health Literature, Medical Literature Analysis and Retrieval System Online, and psycINFO using combinations of keywords; and (3) review of cited references and hand‐searching of selected journals. Evidence was selected using predefined inclusion criteria. Papers included two surveys, one qualitative study and one case study. An integrative review methodology was used to synthesize the evidence presented. Analysis revealed three overriding themes: quality of life, shattered families and rallying around. These illuminated the experiences of family members. These papers revealed families under strain and often at breaking point but with the resolve to pull together if the right support is available. This review concludes that further research is needed to investigate the effects of hoarding on family members and how these may best be met.